7th european metallurgical conference EMC 2013 - Stopić, Srećko R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
From June 23 – 26, 2013, the GDMB Society for Mining, Metallurgy, Resource and Environmental Technology organized 7th European Metallurgical Conference (EMC 2013) in Weimar, Germany. The previous European metallurgical conferences were organized by  the GDMB in Friedrichshafen (2001), Hanover (2003), Leipzig (2005), Duesseldorf (2007), Innsbruck (2009), and Duesseldorf (2011). The GDMB is a non-profit organization from Clausthal, Germany,,focused on combining science with practical experience in metallurgy, mining, materials engineering, mineral processing, recycling and refining of metals, and  manufacturing of semi- and finishing products. The European Metallurgical conference EMC is one of the most well-known conferences worldwide in the field of non-ferrous metallurgy and is attended regularly by decision makers from industry and universities. The scientific program contained 6 plenary lectures and more than 130 presentations. An extensive poster exhibition was held, during which the authors had an opportunity to introduce their posters to the entire plenum as a part of a brief presentation., The € 500 worth “Poster Award EMC 2011 was awarded to Christoph Pichler from the Montan-University in Leoben, Austria. Not only the most important European countries were represented here, but also more than one third of the lecturers were from countries outside Europe (Canada, Japan, China, USA, South Africa, Australia). The origin of the participants reflects the aim of the organizers: to make this conference a worldwide platform for the scientific exchange of experience and information. The scientific presentations of the conference are presented in Proceedings: Vol. 1: Copper, Precious Metals, Waste effluents Treatment/ Biohydrometallurgical applications; Process Metallurgy, Bridging Non-Ferrous and Ferrous Metallurgy; Vol. 2: Lead and Zinc, Light metals, Sustainable technologies, Sustainable of non-ferrous metals production, Process Control/Process Modelling, Waste heat recovery by ORC Power Generation Vol. 3: General Hydrometallurgy, General Pyrometallurgy, Vessel Integrity, Process Gas Treatment; Recycling The plenary lectures will be published in the scientific journal “World of Metallurgy – ERZMETALL”, published by GDMB. The next 8th European Metallurgical Conference will be held between June 14 and June 17, 2015 in Duesseldorf.
Keywords: nonferrous metallurgy; recycling; hydrometallurgy; metal; environmental protection